ISOLASI DAN UJI AKTIVITAS ANTIBAKTERI MINYAK ATSIRI DARI RIMPANG LENGKUAS (Alpinia galanga L.) - Oka Adi Parwata, I M.; Sastra Dewi, P. Fanny (Jurnal Kimia (Journal of Chemistry); Vol. 2, No. 2 Juli 2008, 2012)
Isolation and antibacterial activity test of the languas rhizomes (Alpinia galanga L.) essential oil was carried out The extract was yellow in colour with a volume of 3,5 mL. The activity test on E. coli bacteria at concentrations 100 ppm and 1000 ppm showed a retardation area of 7 mm and 9 mm in diameters. At 1000 ppm it retarded S. aureus bacteria to a diameter of 7 mm. Gas Chromatography – Mass Spectrometer data show that the essential oil of the languas rhizomes contains mainly 8 components : Dlimonen; Eukaliptol; 3-sikloheksen-1-ol, 4-metil-1-(1-metietil); Fenol, 4-(2-profenil)-asetat; 2,6-oktadien-1-ol, 3,7- dimetil-asetat; 1,6,10-dodekatrien, 7,11-dimetil-3-metilen; Pentadesen; sikloheksen, 1-metil-4-(5-metil-1-metilen-4- heksenil.
Keywords: antibacterial, essential oil, Alpinia galanga L.